Butterfly Species (Lepidoptera) in Forest Area of Namo Village, Kulawi District, Sigi Regency - Uzaini Nur Rahma; Bustamin Bustamin; Manap Trianto; Fatmah Dhafir; Raya Agni; Abd Rauf (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Butterflies (Lepidoptera) are one of the insect groups that play an important role in maintaining ecosystem balance, particularly as pollinators of various flowering plants and as indicators of environmental conditions. This study aimed to identify and describe butterfly species (order: Lepidoptera) found in the forest area of Namo Village, Kulawi District, Sigi Regency. The research employed a descriptive method with an exploratory (survey) technique. Sampling was conducted at three different observation stations. Field data were collected over three days, with two sampling periods per day, from 07:00 to 11:00 and 14:00 to 17:00 local time (WITA). Samples were collected using insect nets and subsequently identified based on morphological characteristics. The results of the study revealed 27 butterfly species belonging to four major families. These families are Nymphalidae (17 species), Papilionidae (6 species), Pieridae (3 species), and Lycaenidae (1 species). The diversity analysis indicated that the family Nymphalidae had the highest number of species. Environmental factors, such as the abundance of host plants in the genus Lantana and host plants of the genus Mangivera, as well as abiotic conditions including an average temperature of 27°C, humidity of 70.33%, and light intensity of 786 cd, were strongly suspected to support the high variation in butterfly species.